2020
DOI: 10.1093/socpro/spaa006
|View full text |Cite
|
Sign up to set email alerts
|

Racial Valuation: Cultural Gatekeepers, Race, Risk, and Institutional Expectations of Success and Failure

Abstract: Racial inequality persists in culture industries, despite increases in representation. Focusing on the Hollywood film industry, this research analyzes written correspondence to understand how, in their discourses, cultural workers as intermediaries or gatekeepers construct ideas about race to make predictions about economic value, success, and failure of cultural products. Findings demonstrate that cultural workers make racial valuations, or race-based judgments about the economic worth of cultural products—in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Like agents and other personnel in such industries as fashion (Mears, 2010(Mears, , 2011 book publishing (Childress & Nault, 2019) or Hollywood cinema (Erigha, 2019(Erigha, , 2020Simon, 2019), the industry figures I interviewed understood and valued diversity in limited ways. When diversity was discussed, it was often couched within broader conversations related to brand revenue and market reach, suggesting that inclusion is useful insofar as it can be commodified.…”
Section: Discussionmentioning
confidence: 99%
“…Like agents and other personnel in such industries as fashion (Mears, 2010(Mears, , 2011 book publishing (Childress & Nault, 2019) or Hollywood cinema (Erigha, 2019(Erigha, , 2020Simon, 2019), the industry figures I interviewed understood and valued diversity in limited ways. When diversity was discussed, it was often couched within broader conversations related to brand revenue and market reach, suggesting that inclusion is useful insofar as it can be commodified.…”
Section: Discussionmentioning
confidence: 99%
“…Female and male actors rely on the support of these gatekeepers when being offered a role and negotiating their compensation for a specific movie project (Vogel, 2020). Many Hollywood gatekeepers are male (Erigha, 2021), and prior research has shown that men demonstrate a pro-male bias even in gender-mixed occupations (Erlandsson, 2019). Consequently, the movie industry's current economic and social setting can explain why the significant difference in the mean salaries of female and male actors still exists.…”
Section: Gm 386mentioning
confidence: 99%
“…Dent (2020) further explored how class-based practices associated with motherhood have an influence on how all women are devalued as creative workers, an effect in direct contrast to men whose employment value increases following parenthood. In addition to gender inequalities, enduring racial inequalities also remain entrenched throughout the CCI (Erigha, 2019(Erigha, , 2021Saha, 2018). Erigha (2019) found that despite increasing racial diversity and post-racial discourses, black directors in Hollywood were disproportionately located on the margins, underrepresented in lucrative positions at core institutions and on core cultural products.…”
Section: Inequalities In the Creative Workforcementioning
confidence: 99%